Designing English Instructional Model: An Integrated Technology in ESP for Biological Students - Rahmatullah Syaripuddin; Salasiah Ammade (Eduvelop: Journal of English Education and Development, 2023)
This study was based on the students’ needs regarding the instructional model of English teaching at the Biology Department. The objective of this study was to design English materials by combining YouTube and ABA (American and British Academy) Applications based on the students' needs analysis. The study was mixed-method research with the subject of the research was Biological students of Muhammadiyah University of Parepare, Indonesia. The result of the study was the instructional model focused on input, process, and output. In the input, there are goals and skills; in the process, there are learning activities and venues and in the output there is learning outcomes. The skills are listening, speaking, reading, and writing. Every skill consists of five activities. Listening skill consisted of five activities, namely hearing, understanding, remembering, responding, and evaluating. Speaking skill consisted of apprehending, synthesizing, analyzing, and evaluating. Reading skill consisted of reading, generating, comprehending, discussing, and evaluating. Writing consisted of pre-writing, composing, feedbacking, revising, and evaluating. There were two venues of the model. They were indoor and outdoor. Besides, the learning outcomes focused on cognitive, affective, and psychomotor